2015
DOI: 10.1200/jco.2014.60.2219
|View full text |Cite
|
Sign up to set email alerts
|

SWOG S0809: A Phase II Intergroup Trial of Adjuvant Capecitabine and Gemcitabine Followed by Radiotherapy and Concurrent Capecitabine in Extrahepatic Cholangiocarcinoma and Gallbladder Carcinoma

Abstract: Purpose The role of postoperative therapy in extrahepatic cholangiocarcinoma (EHCC) or gallbladder carcinoma (GBCA) is unknown. S0809 was designed to estimate 2-year survival (overall and after R0 or R1 resection), pattern of relapse, and toxicity in patients treated with this adjuvant regimen. Patients and Methods Eligibility criteria included diagnosis of EHCC or GBCA after radical resection, stage pT2-4 or N+ or positive resection margins, M0, and performance status 0 to 1. Patients received four cycles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
160
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(174 citation statements)
references
References 36 publications
8
160
3
3
Order By: Relevance
“…Results of a multi-institutional, single-arm phase II study 86 demonstrated the safety and promising efficacy of adjuvant therapy consisting of gemcitabine plus capecitabine followed by conformal EBRT with concurrent capecitabine for patients with resected pCCA/dCCA and gallbladder cancer. The majority of patients (81%) received IMRT 86 .…”
Section: The Evolving Role Of Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a multi-institutional, single-arm phase II study 86 demonstrated the safety and promising efficacy of adjuvant therapy consisting of gemcitabine plus capecitabine followed by conformal EBRT with concurrent capecitabine for patients with resected pCCA/dCCA and gallbladder cancer. The majority of patients (81%) received IMRT 86 .…”
Section: The Evolving Role Of Radiation Therapymentioning
confidence: 99%
“…Results of a multi-institutional, single-arm phase II study 86 demonstrated the safety and promising efficacy of adjuvant therapy consisting of gemcitabine plus capecitabine followed by conformal EBRT with concurrent capecitabine for patients with resected pCCA/dCCA and gallbladder cancer. The majority of patients (81%) received IMRT 86 . In the 54 patients with resected pCCA/dCCA, the 2-year overall survival and local control rates were 68% and 87%, respectively; no differences in overall survival or DFS were observed between patients with R0 versus R1 resection 86 .…”
Section: The Evolving Role Of Radiation Therapymentioning
confidence: 99%
“…Despite curative‐intent resection, positive ductal resection margins are sometimes confirmed after pathological examination. Adjuvant therapy has been advocated to improve these poor outcomes 66, 67, 68, 69, 70, 71. However, given the rarity of extrahepatic cholangiocarcinoma, most of the data regarding adjuvant therapy have come from small, single‐center studies or retrospective single‐arm reviews.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…However, given the rarity of extrahepatic cholangiocarcinoma, most of the data regarding adjuvant therapy have come from small, single‐center studies or retrospective single‐arm reviews. Recent relatively large studies and systematic reviews/meta‐analyses have suggested that adjuvant chemoradiotherapy, radiotherapy, or chemotherapy are associated with improved survival in patients with biliary tract cancer and high‐risk characteristics, including positive ductal resection margins 66, 67, 68. However, the intention‐to‐treat analyses in all the large randomized clinical studies of adjuvant chemotherapy for biliary tract cancer reported thus far have failed to demonstrate its efficacy 69, 70, 71.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…In contrast, patients with R1 resection or positive lymph nodes could be treated by chemoradiotherapy. The SWOG-S0809 study recently showed that sequential chemotherapy with gemcitabine and capecitabine for 12 weeks followed by radiochemotherapy led to promising results [9]. The further role of adjuvant chemotherapy will be evaluated in three large, currently ongoing phase III studies (BILCAP, PRODIGE-12, ACTICCA-1) in three different European countries (France, Germany, UK).…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%